Integrating Text and Image Analysis: Exploring GPT-4V's Capabilities in Advanced Radiological Applications Across Subspecialties - Felix Busch; Tianyu Han; Marcus R Makowski; Daniel Truhn; Keno K Bressem; Lisa Adams (JMIR Publications, 2024)
This study demonstrates that GPT-4V outperforms GPT-4 across radiology subspecialties in analyzing 207 cases with 1312 images from the Radiological Society of North America Case Collection.